Household Organic Waste Utilization for Hermetia illucens Larvae Cultivation in a Circular Economy - Supriyadi Supriyadi; Dewi Mustikaningtyas; Andhina Putri Heriyanti; Kusmuriyanto Kusmuriyanto; Mochamad Nur Sholikhin; Nishfa Mufatihah (Journal of Community Empowerment, 2026)
Waste management has become a major environmental issue in Semarang City due to population growth and rapid urban development, including in Sendangguwo Village, Tembalang District. The increasing volume of household organic waste requires sustainable management strategies to reduce waste accumulation and support environmental conservation. This community service program aimed to implement a circular economy approach through the establishment of an Organic Waste Bank and the cultivation of Hermetia illucens larvae as a form of organic waste utilization with economic value.The program was carried out in three stages: (1) socialization and education on household organic waste management through the Organic Waste Bank, (2) practical training on Hermetia illucens larvae cultivation, and (3) evaluation of program implementation. Training and mentoring methods were employed, involving the service team and partners from PT BERRSIH as resource persons and facilitators.The results showed that the program successfully established an Organic Waste Bank in Sendangguwo Village and improved community knowledge and skills in managing organic waste and cultivating larvae. The cultivated larvae can be utilized as an alternative feed source for poultry and fish, providing additional economic benefits to the community. In conclusion, the integration of an Organic Waste Bank with Hermetia illucens larvae cultivation effectively supports circular economy practices by reducing household organic waste and creating value-added products. This program contributes to environmental sustainability, community empowerment, and the development of innovative waste management practices for society.